Environment-friendly fast-curing spraying film waterproof coating as well as preparation method and application thereof

By adding specific ingredients to acrylic acid for mixing and prepolymerization, environmentally friendly rapid curing sprayed film waterproof coating is prepared, which solves the problems of complex construction and long curing time of traditional waterproof materials, and achieves environmentally friendly, convenient and efficient waterproofing effects. Suitable for modern building needs.

CN119264749APending Publication Date: 2025-01-07SICHUAN TONGSHEN WATERPROOF ENG CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411605143.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Traditional waterproof materials have problems such as environmental pollution, complex construction and long curing time during construction, which is difficult to meet the needs of modern construction industry for environmental protection, convenience and efficiency.

Method used

A preparation method of environmentally friendly rapid curing sprayed film waterproof coating is adopted. By gradually adding triethanolamine, methacrylic acid, polyethylene glycol, zinc oxide and nanotitanium dioxide to acrylic acid, the reaction temperature is controlled Below 60°C, ensure complete reaction and obtain a waterproof coating with rapid curing characteristics.

Benefits of technology

The coating does not release harmful substances during construction, has the characteristics of rapid curing, significantly improves construction efficiency, provides excellent waterproof performance, is suitable for various building structures, extends the service life of the building, and reduces maintenance costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005129352930000101
    Figure BDA0005129352930000101
  • Figure BDA0005129352930000111
    Figure BDA0005129352930000111
Patent Text Reader

Abstract

The invention relates to the technical field of new materials, and discloses an environment-friendly fast-curing spray film waterproof coating and a preparation method and application thereof.The preparation method comprises the steps that triethanolamine, methacrylic acid, polyethylene glycol, zinc oxide and nanometer titania are gradually added into acrylic acid and stirred to be evenly mixed, and a component A is obtained; sequentially adding ammonium persulfate, 2-ethylhexyl acrylate, a polyacrylate emulsion and a polyurethane emulsion into acrylic acid, uniformly stirring, and carrying out prepolymerization reaction to obtain a component B; and mixing the component A and the component B, controlling the reaction temperature to be 60 DEG C or below, and continuously stirring until the reaction is complete, thereby obtaining the environment-friendly quick-curing spray film waterproof coating. The environment-friendly fast-curing film-spraying waterproof coating has excellent waterproof performance and good environmental adaptability, and can be fast cured in a short time to form a layer of compact waterproof film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new materials, and in particular to an environmentally friendly fast-curing spray-film waterproof coating and a preparation method and application thereof. Background Art

[0002] With the rapid development of the modern construction industry, the demand and standards for waterproof materials are also constantly increasing. Modern waterproof materials must not only have excellent waterproof performance, but also meet the requirements of environmental protection, convenient construction and high efficiency. Although traditional waterproof materials, such as asphalt and polyurethane, have excellent waterproof effects, they also bring a series of problems such as environmental pollution, complicated construction process and long curing time. These problems not only affect construction efficiency, but also have a negative impact on the environment.

[0003] Therefore, it is particularly important to develop a new waterproof coating that is both environmentally friendly and has fast curing properties, while also simplifying the construction process. This new waterproof coating will be able to meet the modern construction industry's demand for high-performance materials, while reducing the burden on the environment and improving construction efficiency, thereby promoting the sustainable development of the entire construction industry. Summary of the invention

[0004] In view of this, the present invention proposes an environmentally friendly fast-curing spray film waterproof coating and its preparation method and application, aiming to overcome the deficiencies of the prior art and provide a new waterproof coating that is both environmentally friendly and has fast curing properties. The coating not only has excellent waterproof performance, but is also environmentally friendly during construction, easy to operate, and has a fast curing speed, which can meet the needs of the modern construction industry for high-performance materials.

[0005] The present invention provides a method for preparing an environmentally friendly fast-curing spray film waterproof coating, comprising:

[0006] Mixing reaction: gradually add triethanolamine, methacrylic acid, polyethylene glycol, zinc oxide and nano titanium dioxide into acrylic acid, keep stirring until completely mixed, and obtain component A;

[0007] Prepolymerization: add ammonium persulfate, isooctyl acrylate, polyacrylate emulsion and polyurethane emulsion to acrylic acid in sequence, stir evenly to carry out prepolymerization reaction, and obtain component B;

[0008] Main polymerization reaction: Mix the A component and the B component, control the reaction temperature below 60° C., continue stirring to ensure complete reaction, and obtain the environmentally friendly fast-curing spray waterproof coating after the reaction is completed.

[0009] Preferably, ammonium persulfate, isooctyl acrylate, polyacrylate emulsion and polyurethane emulsion are added to acrylic acid in sequence, stirred evenly and kept at 50-60° C. to carry out prepolymerization for 10-15 minutes.

[0010] Preferably, the main polymerization reaction further comprises:

[0011] The material obtained after the reaction is completed is cooled to room temperature, and the impurities are removed by sieving to obtain the environmentally friendly fast-curing spray film waterproof coating.

[0012] Preferably, the components A and B are mixed, the reaction temperature is controlled below 60° C., and stirring is continued to ensure that the reaction is complete, and the stirring time is at least 30 minutes.

[0013] Preferably, the weight ratio of acrylic acid, triethanolamine, methacrylic acid, polyethylene glycol, zinc oxide and nano-titanium dioxide is 18-22: 0.3-0.6: 0.5-0.7: 1-1.5: 0.8-1.2: 1.5-2.

[0014] Preferably, the weight ratio of acrylic acid, ammonium persulfate, isooctyl acrylate, polyacrylate emulsion and polyurethane emulsion is 5-7:2.4-2.7:0.3-0.5:2-2.5:1-1.3.

[0015] Preferably, the weight ratio of component A to component B is 2-4:1.

[0016] The present invention also proposes an environmentally friendly fast-curing spray film waterproof coating, and the environmentally friendly fast-curing spray film waterproof coating is prepared by the preparation method of the environmentally friendly fast-curing spray film waterproof coating.

[0017] The invention also proposes an application of the environmentally friendly fast-curing spray film waterproof coating in waterproofing.

[0018] The present invention also provides a waterproof product, which includes the environmentally friendly fast-curing spray waterproof coating.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] The present invention introduces an environment-friendly fast-curing spray-film waterproof coating, which will not release harmful substances during the construction process, is harmless to the environment, and meets the demand of the modern construction industry for environment-friendly materials; the coating has a fast-curing property, can complete the curing process in a short time, significantly improves the construction efficiency, and shortens the construction period; through the optimized preparation method, the preparation process of the coating becomes simple and easy to operate, reduces the construction difficulty, and is convenient for on-site construction personnel to quickly master; the coating has excellent waterproof performance, can effectively prevent water penetration, extend the service life of the building, and reduce maintenance costs; thanks to the environmental protection characteristics and fast-curing performance of the coating, it can be widely used in waterproof projects of various building structures, including roofs, basements, toilets, swimming pools, etc., and has broad market application prospects.

[0021] The coating preparation method and application of the present invention not only improve the performance of waterproof materials, but also promote the sustainable development of the construction industry, which is in line with the current development trend of green buildings and environmental protection. DETAILED DESCRIPTION

[0022] The exemplary embodiments of the present disclosure will be described in more detail below. Although the exemplary embodiments of the present disclosure are shown below, it should be understood that the present disclosure can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present disclosure and to be able to fully convey the scope of the present disclosure to those skilled in the art. It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0023] Example 1 Preparation of environmentally friendly fast curing spray waterproof coating

[0024] 1. Main raw materials and their proportions

[0025] 1. Component A

[0026] Acrylic acid: 20 kg;

[0027] Triethanolamine (analytical grade): 0.4 kg;

[0028] Methacrylic acid industrial grade: 0.5 kg;

[0029] Polyethylene glycol industrial grade (content greater than 98%): 1.5 kg;

[0030] Zinc oxide (nano grade, industrial grade, 1000 mesh): 0.8 kg;

[0031] Nano titanium dioxide: 2 kg.

[0032] 2. Component B

[0033] Acrylic acid: 6 kg;

[0034] Ammonium persulfate (analytical grade): 2.6 kg;

[0035] Isooctyl acrylate (industrial grade, content greater than 98%): 0.3 kg;

[0036] Polyacrylate emulsion: 2.5 kg;

[0037] Polyurethane emulsion (solid content 40%): 1 kg.

[0038] 2. Preparation process

[0039] 1. Preparation of component A

[0040] Add acrylic acid into a reaction kettle, and then add triethanolamine, methacrylic acid, polyethylene glycol, zinc oxide and nano titanium dioxide in proportion.

[0041] Keep stirring at 300 rpm for 10 minutes to ensure that all ingredients are evenly mixed.

[0042] 2. Preparation of component B

[0043] Add acrylic acid into another reaction kettle, and then add ammonium persulfate, isooctyl acrylate, polyacrylate emulsion and polyurethane emulsion in proportion.

[0044] The stirring speed was maintained at 400 rpm, the reaction temperature was controlled at 55±2°C, and the prepolymerization reaction was carried out for 15 minutes to ensure that the components were evenly fused.

[0045] 3. Main polymerization reaction

[0046] Slowly pour component A into the reaction kettle of component B, gradually mix and keep stirring, and control the reaction temperature not to exceed 60°C.

[0047] With sufficient mixing, continue stirring for 30 minutes to ensure that the main polymerization reaction is completely carried out.

[0048] 4. Cooling and filtration

[0049] The reacted material was cooled to room temperature and filtered using a 200-mesh filter to remove impurities and insoluble matter.

[0050] Store the finished product in an airtight container in a cool, dry place away from direct sunlight.

[0051] Example 2

[0052] 1. Raw materials and their proportions

[0053] 1. Component A

[0054] Acrylic acid: 18 kg;

[0055] Triethanolamine (analytical grade): 0.6 kg;

[0056] Methacrylic acid industrial grade: 0.7 kg;

[0057] Polyethylene glycol industrial grade (content greater than 98%): 1.2 kg;

[0058] Zinc oxide (nano grade, industrial grade, 1000 mesh): 1 kg;

[0059] Nano titanium dioxide: 1.5 kg.

[0060] 2. Component B

[0061] Acrylic acid: 7 kg;

[0062] Ammonium persulfate (analytical grade): 2.4 kg;

[0063] Isooctyl acrylate (industrial grade, content greater than 98%): 0.5 kg;

[0064] Polyacrylate emulsion: 2 kg;

[0065] Polyurethane emulsion (solid content 42%): 1.2 kg.

[0066] 2. Preparation process

[0067] 1. Preparation of component A

[0068] Add acrylic acid into a reaction kettle, and then add triethanolamine, methacrylic acid, polyethylene glycol, zinc oxide and nano titanium dioxide in proportion.

[0069] Keep stirring at 300 rpm for 10 minutes to ensure that all ingredients are evenly mixed.

[0070] 2. Preparation of component B

[0071] Add acrylic acid into another reaction kettle, and then add ammonium persulfate, isooctyl acrylate, polyacrylate emulsion and polyurethane emulsion in proportion.

[0072] The stirring speed was maintained at 400 rpm, the reaction temperature was controlled at 55±2°C, and the prepolymerization reaction was carried out for 10 minutes to ensure that the components were evenly fused.

[0073] 3. Main polymerization reaction

[0074] Slowly pour component A into the reaction kettle of component B, gradually mix and keep stirring, and control the reaction temperature not to exceed 60°C.

[0075] With sufficient mixing, continue stirring for 30 minutes to ensure that the main polymerization reaction is completely carried out.

[0076] 4. Cooling and filtration

[0077] The reacted material was cooled to room temperature and filtered using a 200-mesh filter to remove impurities and insoluble matter.

[0078] Store the finished product in an airtight container in a cool, dry place away from direct sunlight.

[0079] Example 3

[0080] 1. Raw materials and their proportions

[0081] 1. Component A

[0082] Acrylic acid: 22 kg;

[0083] Triethanolamine (analytical grade): 0.3 kg;

[0084] Methacrylic acid industrial grade: 0.6 kg;

[0085] Polyethylene glycol industrial grade (content greater than 98%): 1 kg;

[0086] Zinc oxide (nano grade, industrial grade, 1000 mesh): 1.2 kg;

[0087] Nano titanium dioxide: 1.8 kg.

[0088] 2. Component B

[0089] Acrylic acid: 5 kg;

[0090] Ammonium persulfate (analytical grade): 2.7 kg;

[0091] Isooctyl acrylate (industrial grade, content greater than 98%): 0.4 kg;

[0092] Polyacrylate emulsion: 2.2 kg;

[0093] Polyurethane emulsion (solid content 45%): 1.3 kg.

[0094] 2. Preparation process

[0095] 1. Preparation of component A

[0096] Add acrylic acid into a reaction kettle, and then add triethanolamine, methacrylic acid, polyethylene glycol, zinc oxide and nano titanium dioxide in proportion.

[0097] Keep stirring at 300 rpm for 10 minutes to ensure that all ingredients are evenly mixed.

[0098] 2. Preparation of component B

[0099] Add acrylic acid into another reaction kettle, and then add ammonium persulfate, isooctyl acrylate, polyacrylate emulsion and polyurethane emulsion in proportion.

[0100] The stirring speed was maintained at 400 rpm, the reaction temperature was controlled at 55±2°C, and the prepolymerization reaction was carried out for 10 minutes to ensure that the components were evenly fused.

[0101] 3. Main polymerization reaction

[0102] Slowly pour component A into the reaction kettle of component B, gradually mix and keep stirring, and control the reaction temperature not to exceed 60°C.

[0103] With sufficient mixing, continue stirring for 30 minutes to ensure that the main polymerization reaction is completely carried out.

[0104] 4. Cooling and filtration

[0105] The reacted material was cooled to room temperature and filtered using a 200-mesh filter to remove impurities and insoluble matter.

[0106] Store the finished product in an airtight container in a cool, dry place away from direct sunlight.

[0107] Comparative Example 1 does not use nano titanium dioxide and polyacrylate emulsion

[0108] 1. Raw materials and their proportions

[0109] 1. Component A

[0110] Acrylic acid: 20 kg;

[0111] Triethanolamine (analytical grade): 0.5 kg;

[0112] Methacrylic acid industrial grade: 0.6 kg;

[0113] Polyethylene glycol industrial grade (content greater than 98%): 1.5 kg;

[0114] Zinc oxide (nano grade, industrial grade, 1000 mesh): 0.9 kg.

[0115] 2. Component B

[0116] Acrylic acid: 6 kg;

[0117] Ammonium persulfate (analytical grade): 2.6 kg;

[0118] Isooctyl acrylate (industrial grade, content greater than 98%): 0.4 kg;

[0119] Polyurethane emulsion (solid content 42%): 1.1 kg.

[0120] 2. Preparation process

[0121] 1. Preparation of component A

[0122] Add acrylic acid into the reaction kettle, and then add triethanolamine, methacrylic acid and polyethylene glycol in proportion.

[0123] Maintain the stirring speed at 300 rpm for 8 minutes to ensure that the materials are evenly mixed.

[0124] 2. Preparation of component B

[0125] Add acrylic acid into another reaction kettle, and then add ammonium persulfate, isooctyl acrylate and polyurethane emulsion in sequence.

[0126] The stirring speed was maintained at 400 rpm, the temperature was controlled at 57±2°C, and the prepolymerization was stirred for 10 minutes.

[0127] 3. Main polymerization reaction

[0128] Slowly pour component A into component B, gradually mix and keep stirring, and control the temperature not to exceed 60℃.

[0129] After the mixture is fully mixed, stirring is continued for 20 minutes to complete the main polymerization reaction.

[0130] 4. Cooling and filtration

[0131] The reactants were cooled to room temperature and filtered through a 200-mesh filter to remove impurities.

[0132] The finished product should be sealed and stored in a cool place, avoiding high temperature and direct sunlight.

[0133] Comparative Example 2: No zinc oxide powder and bio-enzyme antibacterial agent are used

[0134] 1. Raw materials and their proportions

[0135] 1. Component A

[0136] Acrylic acid: 22 kg;

[0137] Triethanolamine (analytical grade): 0.4 kg;

[0138] Methacrylic acid industrial grade: 0.7 kg;

[0139] Polyethylene glycol industrial grade (content greater than 98%): 1.3 kg;

[0140] Nano titanium dioxide: 1.5 kg.

[0141] 2. Component B

[0142] Acrylic acid: 5 kg;

[0143] Ammonium persulfate (analytical grade): 2.8 kg;

[0144] Isooctyl acrylate (industrial grade, content greater than 98%): 0.6 kg;

[0145] Polyacrylate emulsion: 2.4 kg;

[0146] Polyurethane emulsion (solid content 40%): 1.2 kg.

[0147] 2. Preparation process

[0148] 1. Preparation of component A

[0149] Add acrylic acid into a reaction kettle, and then add triethanolamine, methacrylic acid, polyethylene glycol and nano titanium dioxide in proportion.

[0150] Maintain the stirring speed at 300 rpm for 10 minutes to ensure that the materials are fully mixed.

[0151] 2. Preparation of component B

[0152] Add acrylic acid into another reaction kettle, and then add ammonium persulfate, isooctyl acrylate, polyacrylate emulsion and polyurethane emulsion in sequence.

[0153] The reaction temperature was controlled at 52±2°C, the stirring speed was maintained at 400 rpm, and the prepolymerization reaction was stirred for 10 minutes.

[0154] 3. Main polymerization reaction

[0155] Slowly add component A into component B, mix and stir evenly, and control the temperature not exceeding 60℃.

[0156] Stirring was continued for 25 minutes to complete the main polymerization reaction.

[0157] 4. Cooling and filtration

[0158] After the reaction was completed, the mixture was cooled to room temperature and filtered using a 200-mesh filter to remove impurities.

[0159] Store the finished material tightly and avoid exposure to high temperatures and sunlight.

[0160] Test Example 1

[0161] The materials prepared in Examples 1-3 and Comparative Examples 1-2 were subjected to the following performance tests, including:

[0162] 1. Curing time

[0163] Test method: Spray the coating on the substrate at a specified thickness and record the time from spraying to the surface being dry to the touch (i.e., the surface is not sticky) and completely cured.

[0164] Expected results: Tack-free time should be within 5-10 minutes, and full cure time should be within 30-60 minutes.

[0165] 2. Adhesion

[0166] Test method: According to the GB / T9286 cross-hatch method, use a knife to cut a cross grid on the coating, then stick it with transparent tape and tear it off to observe the peeling condition.

[0167] Expected Results: Adhesion should be Grade 1 or better.

[0168] 3. Tensile strength and elongation

[0169] Test method: Use a tensile tester to test the tensile strength and elongation at break of the coating according to the GB / T528 method.

[0170] Expected results: The tensile strength should be 1.5-2.0MPa and the elongation at break should be more than 200%.

[0171] 4. Water resistance

[0172] Test method: Soak the coating sample in water for 72 hours and observe whether it bubbles, falls off or changes color significantly.

[0173] Expected results: The coating should have no blistering, no peeling, and no obvious changes in the surface.

[0174] 5. Acid and alkali resistance

[0175] Test method: Soak the coating in 0.1M HCl and NaOH solutions for 72 hours, respectively, and observe the changes in the coating.

[0176] Expected results: The coating should not bubble or fall off in acid or alkali solutions, and the color should not change significantly.

[0177] 6. Weather resistance

[0178] Test method: Through the UV aging test, simulate the long-term exposure to ultraviolet rays in the outdoor environment. Usually use the QUV accelerated aging tester to test for 500 hours to observe the aging of the coating.

[0179] Expected results: No significant change in coating color and performance, maintaining good flexibility and waterproof properties.

[0180] 7. Wear resistance

[0181] Test method: Use an abrasion tester to record the wear of the coating under a specific load according to GB / T1768 standard.

[0182] Expected results: wear loss is less than 30mg, and there is no obvious wear on the surface.

[0183] These performance characterization tests and results demonstrate the advantages of the environmentally friendly fast-curing spray film waterproof coating in terms of fast curing, wear resistance, UV resistance, adhesion and ductility. The various properties of the embodiment are significantly better than those of the comparative example, especially in terms of curing time, wear resistance and weather resistance, and meet the high requirements of the spray film waterproof coating.

[0184] The test results are shown in Table 1:

[0185] Table 1

[0186]

[0187]

[0188] From the test results in Table 1, we can see that:

[0189] All performance indicators of Example 1, Example 2 and Example 3 are better than those of Comparative Example 1 and Comparative Example 2. Specifically, the curing time of Examples 1 to 3 is short, and the adhesion, tensile strength, and elongation at break all reach a high level, and they are qualified in terms of water resistance, acid and alkali resistance, and weather resistance. In terms of wear resistance, Examples 1 to 3 also perform better, with lower wear. In contrast, Comparative Examples 1 and 2 perform poorly in terms of curing time, adhesion, tensile strength, elongation at break, and wear resistance, and their water resistance, acid and alkali resistance, and weather resistance do not meet the qualified standards, showing obvious performance deficiencies. This shows that by optimizing the formula and process, the comprehensive performance of the material can be significantly improved to meet more stringent application requirements.

[0190] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing an environmentally friendly fast-curing spray film waterproof coating, characterized in that: include: Mixing reaction: gradually add triethanolamine, methacrylic acid, polyethylene glycol, zinc oxide and nano titanium dioxide into acrylic acid, keep stirring until completely mixed, and obtain component A; Prepolymerization: add ammonium persulfate, isooctyl acrylate, polyacrylate emulsion and polyurethane emulsion to acrylic acid in sequence, stir evenly to carry out prepolymerization reaction, and obtain component B; Main polymerization reaction: Mix the A component and the B component, control the reaction temperature below 60° C., continue stirring to ensure complete reaction, and obtain the environmentally friendly fast-curing spray waterproof coating after the reaction is completed.

2. The method for preparing the environmentally friendly fast-curing spray film waterproof coating according to claim 1, characterized in that: Add ammonium persulfate, isooctyl acrylate, polyacrylate emulsion and polyurethane emulsion to acrylic acid in sequence, stir evenly and keep the temperature at 50-60°C to carry out prepolymerization reaction for 10-15 minutes.

3. The method for preparing the environmentally friendly fast-curing spray film waterproof coating according to claim 1, characterized in that: The main polymerization reaction also includes: The material obtained after the reaction is completed is cooled to room temperature, and the impurities are removed by sieving to obtain the environmentally friendly fast-curing spray film waterproof coating.

4. The method for preparing the environmentally friendly fast-curing spray film waterproof coating according to claim 1, characterized in that: The components A and B are mixed, the reaction temperature is controlled below 60° C., and stirring is continued to ensure that the reaction is complete. The stirring time is at least 30 minutes.

5. The method for preparing the environmentally friendly fast-curing spray film waterproof coating according to claim 1, characterized in that: The weight ratio of acrylic acid, triethanolamine, methacrylic acid, polyethylene glycol, zinc oxide and nano titanium dioxide is 18-22: 0.3-0.6: 0.5-0.7: 1-1.5: 0.8-1.2: 1.5-2.

6. The method for preparing the environmentally friendly fast-curing spray film waterproof coating according to claim 1, characterized in that: The weight ratio of acrylic acid, ammonium persulfate, isooctyl acrylate, polyacrylate emulsion and polyurethane emulsion is 5-7: 2.4-2.7:0.3-0.5:2-2.5:1-1.3。 7. The method for preparing the environmentally friendly fast-curing spray film waterproof coating according to claim 1, characterized in that: The weight ratio of component A to component B is 2-4:

1.

8. An environmentally friendly fast-curing spray film waterproof coating, characterized in that: The environmentally friendly fast-curing spray waterproof coating is prepared by the preparation method of the environmentally friendly fast-curing spray waterproof coating described in any one of claims 1-7.

9. Use of the environmentally friendly fast-curing spray waterproof coating according to claim 8 in waterproofing.

10. A waterproof product, characterized in that: The waterproof product includes the environmentally friendly fast-curing spray waterproof coating as described in claim 8.